Optimalisasi Nilai-Nilai Sosial Keagamaan Siswa melalui Metode Role Playing - Sukamto (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2021)
This study aims to describe efforts to optimize students' socio-religious values through conceptual role-playing methods. This study uses library research, in which research objects are usually explored through a variety of library information (books, encyclopedias, scientific journals, newspapers, magazines, and documents). Data sources in library research are primary sources and secondary sources. The data collection technique is a documentation technique. The analysis technique used is deductive, descriptive method and document analysis. The results of the study are that the implementation of role-playing activities can be carried out with 4 steps, namely environmental steps, steps before playing, steps during play, and steps after playing. The role-playing method can improve the development of students' socio-religious values. The increased social and religious development of students is evidenced by children who like to help friends and adults, children who want to share with others, children who are used to being friendly, children who are accustomed to respecting elders, children who listen and pay attention when their friends talk, children can distinguish between right and wrong actions. wrong, able to be responsible, children can work together, children can recognize their feelings and manage them naturally, and children can show empathy.